Effects of supplementation of desert grass (hummra) on its utilization by Sudan Desert sheep and Desert goats - Mustafa, E.E. (1979)
Due to acute shortage of quality feeds the majority or ruminants have to depend mainly on poor quality roughages. Two main drawbacks of such roughages are low ad libitum consumption and poor utilization. In the Sudan hummra is characteristic of the grass dominant in the pasture and as the bulk of animal population in the Sudan is in the hands of nomads, livestock depend entirely on these grasses, which are low in nitrogen content and are presumably inadequate for meeting the growth requirements of these animals. So limited supplementation experiments were designed to see the effects of supplementation of hummra with molasses, minerals, urea and cotton seed cake (Either separately or together) on its utilization by desert sheep and desert goats and the performance of these animals. Twenty-five young male desert sheep and a similar number of young male desert goats were divided to five groups each, which were matched according to body weight. Group I was fed chopped hummra, group II: chopped hummra +10%molasses, Group III: chopped hummra + 10% molasses +3% minerals + vitamins, Group IV: chopped hummra +10% molasses + 3% minerals + vitamins +2.7% urea and Group V fed chopped hummra +10% molasses +3% minerals + vitamins +25% cotton seed cake. Feeding trials were carried out for 6 to 9 weeks. Water was available all the time. The following parameters were used for measuring the extent of utilization of unsupplemented and supplemented desert grass and the effect of supplementation on the performance of desert sheep and desert goats: 1. Feed intake and dry matter digestibility. 2. Nitrogen balance. 3. Growth (Body weight changes) 4. Blood chemical composition. 5. Rumen liquor chemical composition. 6. Dressing percentage. In the light of the above measurements a comparison was made in the efficiency of feed utilization by desert sheep and desert goats. The results obtained are as follows: 1. Feed intake and apparent dry matter digestibility: supplementation with molasses alone or with molasses plus minerals had no significant effect. Supplementation with urea cotton seed cake increased food intake and dry matter digestibility. 2. Feeding hummra alone or hummra plus molasses and mineral mixture, resulted in negative nitrogen balance. Supplementation with urea or cotton seed cake resulted in a positive nitrogen balance which was greater in case of cotton seed cake supplementation than urea supplementation. 3. Growth: In both sheep and goats the group fed grass only and group fed grass plus molasses or molasses and minerals failed to growth or even to maintain body weight. Group IV which received urea supplement managed to maintain its body weight. The only group of sheep and goats which showed positive growth was the group supplemented with protected protein in the form of cotton seed cake. 4. The blood constitutes (total serum protein, albumin, urea, glucose, inorganic phosphorous, magnesium and calcium) were not much affected by the various treatments. The major change occurred in serum urea level, which was significantly higher in groups fed urea and cottonseed cake.5. Supplementation with cotton seed cake or urea resulted in increased levels of ammonia and total volatile fatty acids in rumen fluid. PH decreased as the levels of total volatile fatty acids increased and showed significant variation. The other rumen liquor components studied (Na, K, osmolarity) showed no significant difference between treatments in both sheep and goats. 6. Supplementation with urea or cotton seed cake resulted in a significant increase in dressing percentage in both sheep and goats but there was no marked difference between feeding hummra alone, hummra plus molasses or molasses plus minerals. The efficiency of utilization of unsupplemented and supplemented desert grass was essentially similar in both sheep and goats. However, supplementation with urea and cotton seed cake was rather more beneficial to goats than sheep. It is concluded from the results of this work than desert grass (hummra) is inadequate for meeting the growth requirements of young desert sheep and desert goats. Supplementation with molasses or molassess and minerals did not improve the utilization of this low-quality roughage. Addition of urea (2.7%) to the molasses/minerals supplement improved utilization of desert grass and almost reached the maintenance requirements of both sheep and goats. Supplementation with protected protein in the form of cotton seed cake improved utilization of hummra and resulted in a gain in body weight in both sheep and goats. So it is recommended to use urea as a cheap source of nitrogen supplement for low-quality roughage together with grain or cotton seed cake as a source of protected protein.